Pengaruh Variasi Kecepatan Sirkulasi Udara Terhadap Laju Pengeringan Kayu Pada Dapur Pengering Kayu - Karnowo, Karnowo; Al Janan, Dony Hidayat; Widayat, Widi (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2021)
The aim of this research is to investigate the effect of air circulation speed variations on the rate of wood drying in the wood drying kiln. The research was carried out by installing an exhaust fan at the end of the chimney exiting the oven. The speed of the exhaust fan can be varied. Variations in circulation speed are set from 1 m/s to 8 m/s. The temperature and RH in the oven at each drying stage are maintained stable. The results obtained from the research are as follows. The sample drying rate with four pieces of mahogany wood was found to be an average of 16.6% per hour for all variations. At the greatest speed variation Vcirculation = 8 m/s, the target final moisture content (MC) reaches 4.17%, and at Vcirculation = 1 m/s (lowest), the final MC is 7.67%. So the higher the circulation speed, the greater the drying rate. However, at high circulation speeds, physical damage to the wood will occur, namely cracks on the face and ends of the wood.